Ecocriticism : the essential reader (Routledge, 2015)
"Ecocriticism: The Essential Reader charts the growth of this important field. The first-wave ecocriticism section focuses on key readings from the 1960s to the 1990s. The second-wave ecocriticism section goes on to consider a range of exciting contemporary trends, including environmental justice, aesthetics and philosophy, and globalization.Readings include the work of:Raymond WilliamsJonathan BateTimothy MortonUrsula HeiseLawrence BuellKate SoperCary Wolfeand Kate Rigby.Containing seminal, representative, and contemporary work in the field, this volume and the editorial commentary is designed for use on both undergraduate and postgraduate ecocritical literature courses"--